Respon Tanaman Jagung terhadap Pemupukan Fosfor pada Typic Dystrudepts - Antonius Kasno (UNIVERSITY OF LAMPUNG, 2009)
Response of Maize Plant to Phosphorus Fertilization on Typic Distrudepts (A. Kasno): On the acid soil, phosphorus nutrients become critical for agricultural crops growth. At the present, price of fertilizers significantly increase and fertilizers are not available. These conditions can affect on soil productivity and crop production. The objective of these research were to study the response of maize (Zea mays L.) to phosphate fertilizers on Inceptisol. The research was conducted in Cicadas Village on Typic Dystrudept. Experiment was conducted in a randomized completely block design, with 8 treatments and three replications. Treatments consisted of 6 dosages of P fertilizers, which were P source is SP-36 WIKA Agro 0, 10, 20, 40, 60 and 80 kg ha-1. SP-36 and Tunisia rock phosphate (40 kg P ha-1) were used for standard. Pioneer 12 variety of maized was used as an indicator. Plot size was 5 m x 6 m and the maize was planting with distance of 75 cm x 20 cm with one seed per hole. The results showed that organic C and N, P (extracted by Bray 1), K and CEC on the soil were low. Phosphate fertilizers significantly increased which was P extracted by HCl 25% from 24 to 67 mg P 100 g-1 soil and which were extracted by Bray 1 increased from 0,87 to 63.31 mg P kg-1 soil. Phosphate fertilizers significantly increased plant height from 175.2 cm become to 221.1 cm. Plant height of maize using SP-36 WIKA Agro fertilizer (210.6 cm) was similar to plant heigh using SP-36 fertilizer (213.4 cm) but less height from Tunisia rock phosphate. The yield of maize on SP-36 WIKA Agro (4.94 t ha-1) were linely higher than SP-36 (4.69 t ha-1), significantly was higher than that of Tunisia rock phosphate. Maximum dosage of SP-36 fertilizer was 66.67 kg P ha-1, and optimum dosage was 42 kg P ha-1. Value of Relative Agronomic Effectiveness SP-36 WIKA Agro fertilizer was heigher than SP-36.